Validation into Spanish of a Scale to Detect the Post-intensive Care Syndrome - Narváez Martínez, Mario Andrés; Henao Castaño, Ángela María (Investigación y Educación en Enfermería, 2023)
Objective. This work sought to validate the Spanish version of the scale Healthy Aging Brain-Care Monitor (HABC-M) scale as clinical tool to detect the Post-intensive Care Syndrome. Methods. Psychometric study, conducted in adult intensive care units from two high-complexity university hospitals in Colombia. The sample was integrated by 135 survivors of critical diseases with mean age of 55 years. The translation of the HABC-M was carried out through transcultural adaptation, evaluating content, face, and construct validity and determining the scale’s reliability. Results. A replica was obtained of the HABC-M scale in its version into Spanish, semantically and conceptually equivalent to the original version. The construct was determined through confirmatory factor analysis (CFA), evidencing a three-factor model comprised of the subscales: cognitive (6 items), functional (11 items), and psychological (10 items), with a confirmatory factor index (CFI) of 0.99, a Tucker Lewis index (TLI) of 0.98, and an approximate root-mean-square error (RMSE) of 0.073 (90% CI: 0.063 – 0.084). Internal consistency was determined through Cronbach’s alpha coefficient, obtaining 0.94, (95% CI 0.93 – 0.96). Conclusion. The Spanish of the HABC-M scale is a tool with adequate psychometric properties, validated and reliable to detect the Post-intensive Care Syndrome.